2019
DOI: 10.1111/pace.13845
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of catheter ablation combined with left atrial appendage occlusion for nonvalvular atrial fibrillation: A systematic review and meta‐analysis

Abstract: Atrial fibrillation (AF) is currently the most prevalent arrhythmia in clinical practice, with stroke being one of its major complications. Combining catheter ablation and percutaneous left atrial appendage occlusion (LAAO) into a "one-stop" intervention could reduce stroke incidence in selected high-risk patients and, at the same time, relieve AF symptoms in a single procedure.This meta-analysis analyzed the efficacy and safety of catheter ablation combined with LAAO for nonvalvular AF. PubMed, EMBASE, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…The pooled rates of device embolization and other bleeding events were as low as 0.01, and the average annualized bleeding rate reduction was as high as 60.3%. The results of the long-term adverse events were likely to previous studies, 15,16 indicating this combined procedure had a reliable performance on safety.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The pooled rates of device embolization and other bleeding events were as low as 0.01, and the average annualized bleeding rate reduction was as high as 60.3%. The results of the long-term adverse events were likely to previous studies, 15,16 indicating this combined procedure had a reliable performance on safety.…”
Section: Discussionsupporting
confidence: 54%
“…In the case of efficacy outcomes, the results showed the combined procedure had a high rate of 1.00 in long-term successful sealing of LAAC, similar to recent meta-analysis results with a successful sealing rate of 0.98. 16 The pooled rate of ischemic stroke/TIA/systemic embolism during follow-up was as low as 0.01. Importantly, the average annualized stroke rate reduction was as high as 79.7%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent study from China revealed that the immediate success rate of LAAC after CA was 100 percent 21 . What is more, a meta‐analysis of 18 studies showed that the one‐stop procedure had a 98% procedural success rate of LAAC 22 . Different success rate of device implantation in the combination procedure may be associated with patient volume and operator's experience.…”
Section: Important Issues To Be Considered In the Combination Proceduresmentioning
confidence: 99%
“…Recently, Jiang et al conducted a meta-analysis on the efficacy and safety of CA combined with LAAO, concluding that a single procedure combining these 2 approaches is a feasible strategy with significant levels of efficacy and safety. 3 Therefore, one-stop intervention may become increasingly common in clinical practice in the future.…”
Section: Introductionmentioning
confidence: 99%